Improving Dementia Long-Term Care A Policy Blueprint - Shih, Regina A. (RAND Corporation, 2014)
In 2010, 15 percent of Americans older than age 70 had dementia. By 2050, the number of new dementia cases among those 65 and older is expected to double. This blueprint outlines policy options to help decisionmakers improve dementia long-term services and supports (LTSS) by promoting earlier detection, improving access to LTSS, promoting person- and caregiver-centered care, supporting caregivers, and reducing dementia LTSS costs.